The effect of physical aging, starch particle size, and starch oxidation on thermal-mechanical properties of poly(lactic acid)/starch composites - Moura, Ricardo Acioli (Kansas State University, 2006)
Poly(lactic acid) (PLA), a synthetic biopolymer, is a promising substitute of some petroleum-based polymers due to its mechanical and biodegradable properties. But, because of the high cost of PLA (compared to those petroleum plastics for disposable application), starch has been incorporated into PLA to reduce cost and accelerate the biodegradability rate of the composites. But, the addition of starch as filler to PLA decreased mechanical performance of the composite. The addition of methylenediphenyl diisocyanate (MDI) into PLA/starch blends improved drastically the mechanical properties of the composite. Results from thermal-degradation analysis showed that PLA had the highest Arrhenius activation energy and strongest thermal endurance of all samples, followed by PLA/starch/MDI and PLA/starch. Aged samples exposed to fluctuating humidity storage conditions significantly decreased their performance. But, storing the samples in plastic bags could minimize degradation of properties. PLA and its composites with starch would not significantly affect application function when they are stored in controlled environment. PLA and PLA/starch based composites sealed in plastic bags can be stored in fluctuating humidity conditions (30-90% RH) for up to 30 days. Tensile strength, elongation, and damping increased with average particle size of starch granules (APS). But, declination of these properties was detected with APS larger than 45 mm. Crystallinity increased as the APS decreased. Young’s modulus, storage modulus, and moisture absorption were not significantly affected by the starch APS. The use of MDI as a coupling agent altered the role of starch APS on those properties of poly(lactic acid)/starch composite. The oxidation of the primary alcohol group on C6 of starch molecules up to 10% degree of substitution did not significantly affect the mechanical properties of PLA/starch/MDI, but the composites showed a reduced inelastic deformation (tensile curve) and significant increase in storage modulus and damping. Results suggest that a substitution of hydroxyl group on C6 of starch molecules for carboxyl group (up to 10%) increased the strengthening effect of MDI enough to reduce inelastic deformation of the composites upon load, but not enough to enhance mechanical properties.
Keywords: Poly(lactic acid); Starch; Physical aging; Particle size; Oxidation; Composites; Agriculture, Food Science and Technology (0359); Agriculture, General (0473)